Democratic Erosion and Democratic Resilience in Central Europe during COVID-19 - Petra Guasti (Czech Journal of International Relations, 2021)
What are the effects of populists in power on democracy during a pandemic? The paper seeks to distinguish the extent to which the COVID-19 pandemic can (not) be traced to democratic erosion and democratic resilience. Are the changes in the quality of democracy resulting from political leaders' actions or rather a path-dependent continuation of previous trends? This contribution focuses on two paths – democratic erosion and democratic resilience – in the Visegrad Four countries (the Czech Republic, Hungary, Poland, and Slovakia), which are all governed by populist leaders. It builds on previous literature that focused principally on the first wave of the pandemic by focusing on institutional guardrails and accountability (vertical, horizontal, and diagonal) during the 18 months of the pandemic. It seeks to answer the following question: What conditions are necessary and sufficient to prevent democratic erosion?